2018
DOI: 10.3390/ijerph15091991
|View full text |Cite
|
Sign up to set email alerts
|

Faithful Families Cooking and Eating Smart and Moving for Health: Evaluation of a Community Driven Intervention

Abstract: Background: There is an increasing need to adapt and use community interventions to address modifiable behaviors that lead to poor health outcomes, like obesity, diabetes, and heart disease. Poor health outcomes can be tied to community-level factors, such as food deserts and individual behaviors, like sedentary lifestyles, consuming large portion sizes, and eating high-calorie fast food and processed foods. Methods: Through a social ecological approach with family, organization and community, the Faithful Fam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Previous work in this community highlighted a cultural value for assisting neighbors in need (Cardarelli et al, 2020), indicating the importance of social cohesion tied to geography. Although some progress has been made in nutritional confidence and self-efficacy, results have shown a limited impact on sustainable behavior changes (Torrence et al, 2018). Given our findings, health promotion interventions in this population should prioritize community-level programs, leveraging collectivism over individual initiatives and integrating cultural values into practice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in this community highlighted a cultural value for assisting neighbors in need (Cardarelli et al, 2020), indicating the importance of social cohesion tied to geography. Although some progress has been made in nutritional confidence and self-efficacy, results have shown a limited impact on sustainable behavior changes (Torrence et al, 2018). Given our findings, health promotion interventions in this population should prioritize community-level programs, leveraging collectivism over individual initiatives and integrating cultural values into practice.…”
Section: Discussionmentioning
confidence: 99%
“…The socio-ecological approach explains the interaction between different factors that lead to healthy or unhealthy behavior and decisions. This approach also organizes these factors in different levels [24,25]. Level 3: Factors determined by governmental structures, production systems, laws and politics.Level 2: Factors determined by the conditions in which people´s day to day activities take place.…”
Section: Introductionmentioning
confidence: 99%
“…The socio-ecological approach explains the interaction between different factors that lead to healthy or unhealthy behavior and decisions. This approach also organizes these factors in different levels [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also found an association when examining the food environment with all-cause mortality ( Sun, Liu et al, 2020 ; Tani et al, 2018 ; Wang et al, 2014 ). This is important to note because low-access areas tend to have fewer supermarkets and grocery stores, which often results in a reduced intake of fruits, vegetables, whole grains, and nutritionally dense foods ( Torrence et al, 2018 ). Additionally, low-access areas mainly consist of convenience and corner stores that typically allocate less than five feet of shelf space for quality foods but nearly 300 feet of shelf space for beverages and snack foods ( Caspi et al, 2017 ).…”
mentioning
confidence: 99%